(untitled) (International Journal of Medical and Surgical Sciences, 2020)
This study had as a goal to analyze the prevalence of suggestive images of atheromatous calcification in the common carotid artery, aiming to relate it to age, sex, antimere and to analyze the morphology of its calcification, through digital panoramic radiographs of the jaws. It’s an observational, transversal and retrospective study, on which there were analyzed 4.837 radiographs, that came from the files of a dental radiology private service in the city of Cabo de Santo Agostinho-PE, Brazil, referring to the period between 2011-2017. The morphology of the calcified atheromatous plaque was classified in: Grade I – normal (plaque not displayed); Grade II – intimal thickening; Grade III – simple plaque (less than 5mm thick); Grade IV – complex plaque (over 5mm thick) and Grade V – debris (irregular plaque with moving projections). The data collected was expressed in absolute values and frequency, analyzed through the chi-square, considering p< 0,05. Of the analyzed radiographs, 1.321 filled the eligibility criteria, of these 51 (3,8%0 presented suggestive image of atheromatous plaque, 71% were of the female sex (p = 0,003), 45% were at the age range between 5th and 6th decade of life (p= 0,001), most of the identified plaques were unilateral, to the left (p=0,02) and 76% were morphologically classified as grade III (less than 5mm thick). In this study, it was verified the low prevalence of suggestive images of atheromatous in carotid artery, with greater occurrence on the female sex, between the 5th and 6th decade of life, unilaterally, to the left and morphologically classified in grade III.